Gold nanorod-assembled ZnGa2O4:Cr nanofibers for LED-amplified gene silencing in cancer cells. Issue 28 (4th July 2018) - Qin, Lun; Yan, Peijian; Xie, Congkun; Huang, Jie; Ren, Zhaohui; Li, Xiang; Best, Serena; Cai, Xiujun; Han, Gaorong
Abstract : A localized therapeutic system, consisting of gold nanorods (Au NRs) loaded with hTERT siRNA assembled on the surface of ZnGa2 O4 :Cr (ZGOC) nanofibers, offers the potential for a LED-induced mild photothermal effect which enhances gene silencing effect in cancer cells. Abstract : Nanoparticles are now commonly used as non-viral gene vectors for RNA interference (RNAi) in cancer therapy but suffer from low targeting efficiency in situ . Meanwhile, localized drug delivery systems do not offer the effective capability for intracellular gene transportation. We describe here the design and synthesis of a localized therapeutic system, consisting of gold nanorods (Au NRs) loaded with hTERT siRNA assembled on the surface of ZnGa2 O4 :Cr (ZGOC) nanofibers. This composite system offers the potential for a LED-induced mild photothermal effect which enhances the phagocytosis of Au NRs carrying siRNA and the subsequent release of siRNA in the cytoplasm. Both phenomena amplify the gene silencing effect and consequently offer the potential for a superior therapeutic outcome.